Co-regulated ceRNA network mediated by circRNA and lncRNA in patients with gouty arthritis - Yanqiu Xu; Jiayu Tian; Miao Wang; Jinkun Liu; Wenfu Cao; Bin wu (BMC, 2024)
Abstract Numerous studies have demonstrated the involvement of messenger RNAs (mRNAs) and non-coding RNAs, including long non-coding RNAs (lncRNA), circular RNAs (circRNAs) and microRNA (miRNAs), in gouty arthritis onset; however, the regulatory mechanism has not yet been elucidated. Here, we applied whole-transcriptome sequencing to identify the differentially expressed circRNAs, lncRNAs, miRNAs and mRNAs between the gout patients and normal people, and constructed co-regulated networks of circRNAs and lncRNAs according to the competitive endogenous RNA (ceRNA) theory for gouty arthritis onset to improve our understanding of the pathogenesis of this disease. The most significant finding of this study is the co-regulated ceRNA network of circRNAs and lncRNAs in gouty arthritis. The circRNA novel_circ_0030384 and the lncRNAs AAMP, TRIM16, PKN1, XLOC_184579 and XLOC_189826 were upstream genes in the co-regulated network. These upstream genes upregulated miR550a-5p and miR550a-3-5p, which downregulated PSME1 and FERMT3 expression. These mRNAs participated in proteasome dynamics, antigen processing and presentation, and platelet activation, which are associated with inflammation in gouty arthritis. In addition, the circRNA and lncRNAs upregulated miR550a-5p, which downregulated GRK2 and OS9 expression. Also, it proved that the down-regulated of PSME1, FERMT3, GRK2 and OS9 can aggravate gouty arthritis in vitro. In summary, these genes mediate inflammation in gouty arthritis through chemokine signaling to regulate neutrophil function.